2021
DOI: 10.1016/j.ejrad.2021.109650
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between lung ultrasound and chest CT patterns with estimation of pulmonary burden in COVID-19 patients

Abstract: Purpose The capability of lung ultrasound (LUS) to distinguish the different pulmonary patterns of COVID-19 and quantify the disease burden compared to chest CT is still unclear. Methods PCR-confirmed COVID-19 patients who underwent both LUS and chest CT at the Emergency Department were retrospectively analysed. In both modalities, twelve peripheral lung zones were identified and given a Severity Score basing on main lesion pattern. On CT scans the well-aerated lung vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…As recent studies have confirmed high sensitivity of LUS for COVID-19 pneumonia, this limitation unlikely has significant impact on disease prevalence, although we acknowledge that severity score concordance between CT and LUS vary. 8 This study also has several strengths. This was the first study to investigate the prevalence of pulmonary findings in outpatients with SARS-CoV-2 infection using LUS, and the largest outpatient COVID-19 study of the general population to date.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As recent studies have confirmed high sensitivity of LUS for COVID-19 pneumonia, this limitation unlikely has significant impact on disease prevalence, although we acknowledge that severity score concordance between CT and LUS vary. 8 This study also has several strengths. This was the first study to investigate the prevalence of pulmonary findings in outpatients with SARS-CoV-2 infection using LUS, and the largest outpatient COVID-19 study of the general population to date.…”
Section: Discussionmentioning
confidence: 96%
“…3 Given the lack of radiation, ease of use, portability and low cost, 4 ultrasound may be a useful tool in the management of COVID-19. COVID-19 pneumonia is commonly located in a subpleural, peripheral and basilar distribution on CT imaging, [5][6][7][8] which makes it amenable to detection by lung ultrasound (LUS). Protocols targeting the posterior and lateral aspects of lungs allow detection of the disease and maximise provider safety.…”
Section: Introductionmentioning
confidence: 99%
“…B-lines are vertical hyperechoic laser-like rays arising from the pleural line and extended to the edge of the screen, which move with respiration (a sign called lungsliding). The B-line pattern is the most characteristic sign in COVID-19 with different varieties (separated B-lines, focal, multifocal, coalescent, "rocket sign", "light beam"), reported by most of the studies, with a predominantly posterior and inferior distribution [19][20][21][22][23][24]. The B-lines can coexist with A-lines, in the context of good aeration, called spared areas.…”
Section: Lus Techniquementioning
confidence: 99%
“…As a domestic way to treat or decrease the hard breathing associated with COVID-19, we recommend breathing the boiled eucalyptus vapor. This practice with drugs could help patients to overcome the disease (Marzano et al, 2021;Núñez-Gil et al, 2021;Repullo, 2021;Rizzetto et al, 2021).…”
Section: Preventive Measuresmentioning
confidence: 99%